Developmental Evaluation: Applying Complexity Concepts to Enhance Inno vation and Use - Patton, Michael Quinn (Guilford Press, 2010)
Developmental evaluation (DE) offers a powerful approach to monitoring and supporting social innovations by working in partnership with prog ram decision makers. In this book, eminent authority Michael Quinn Pat ton shows how to conduct evaluations within a DE framework. Patton dra ws on insights about complex dynamic systems, uncertainty, nonlinearit y, and emergence. He illustrates how DE can be used for a range of pur poses: ongoing program development, adapting effective principles of p ractice to local contexts, generating innovations and taking them to s cale, and facilitating rapid response in crisis situations. Students a nd practicing evaluators will appreciate the book's extensive case exa mples and stories, cartoons, clear writing style, "closer look" sideba rs, and summary tables. Provided is essential guidance for making eval uations useful, practical, and credible in support of social change.Se e also Developmental Evaluation Exemplars, edited by Michael Quinn Pat ton, Kate McKegg, and Nan Wehipeihana, which presents 12 in-depth case studies.
Keywords: Evaluation; Measurement; Organizational effectiveness; Project management